Analysis of Single Mother Parenting: Analisis Pola Asuh Ibu Tunggal - Azizah Alifia Salsabila; Nurfi Laili (Academia Open, 2022)
A single parent is a parent who alone raises their children without the presence, support or responsibility of their spouse. Mothers must play a major role in the growth and development of children, because mothers are the first teachers who can have a very big influence on their children. Being a single parent with teenage children is a great gift entrusted by the creator, having teenage children means having a big responsibility in guiding them to adulthood. This study aims to describe the model of single mother parenting. The subjects in this study consisted of 2 single mothers, the sample in this study used the snowball sampling technique and met the following criteria: 1) single mothers 2) domiciled in Taman, Sidoarjo. This study uses qualitative research methods with a case study approach. The data collection technique used by the researcher is interviews. The results of this study stated that the two subjects applied the democratic parenting model to their teenage children.. Highlights: Single-parenting challenges: The study focuses on the unique experiences and challenges faced by single mothers in raising their teenage children alone. Democratic parenting: The research highlights the application of the democratic parenting model by single mothers as an effective approach in guiding their teenage children. Qualitative case study: The study employs qualitative research methods, using interviews as the primary data collection technique, to gain in-depth insights into the experiences and parenting practices of the single mothers in the sample. Keywords: single parent, teenage children, democratic parenting, qualitative research, case study